2020
DOI: 10.1007/s00204-020-02682-w
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of primary hepatic non-parenchymal cells in a 3D spheroid model and contribution to acetaminophen hepatotoxicity

Abstract: In addition to hepatocytes, the liver comprises a host of specialised non-parenchymal cells which are important to consider in the development of in vitro models which are both physiologically and toxicologically relevant. We have characterized a 3D co-culture system comprising primary human hepatocytes (PHH) and non-parenchymal cells (NPC) and applied it to the investigation of acetaminophen-induced toxicity. Firstly, we titrated ratios of PHH:NPC and confirmed the presence of functional NPCs via both immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 51 publications
0
32
0
1
Order By: Relevance
“…Other cell types used in combination with hepatocytes to establish in-vitro liver models include the non-parenchymal cell types found in the liver (i.e., Kupffer cells, stellate cells, liver sinusoidal endothelial cells (LSECs), and cholangiocytes), with the aim of recapitulating the liver's multi-cellular environment and paracrine signaling. Similar to PHHs, NPCs can be primary human cells derived from liver resection/biopsies (e.g., NPC liver fractions or isolated Kupffer cells) (32,68,(78)(79)(80)(81). Cancer/ immortalized cell lines can also be used to represent the liver-specific NPCs (82).…”
Section: Establishing In Vitro Liver Models Using Human-based Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other cell types used in combination with hepatocytes to establish in-vitro liver models include the non-parenchymal cell types found in the liver (i.e., Kupffer cells, stellate cells, liver sinusoidal endothelial cells (LSECs), and cholangiocytes), with the aim of recapitulating the liver's multi-cellular environment and paracrine signaling. Similar to PHHs, NPCs can be primary human cells derived from liver resection/biopsies (e.g., NPC liver fractions or isolated Kupffer cells) (32,68,(78)(79)(80)(81). Cancer/ immortalized cell lines can also be used to represent the liver-specific NPCs (82).…”
Section: Establishing In Vitro Liver Models Using Human-based Cellsmentioning
confidence: 99%
“…Endothelial cells and mesenchymal stem cells are also being used in combination with hepatocytes to try to emulate the endodermal, endothelial, and mesenchymal interactions that occur during organogenesis and liver bud formation (83), with human umbilical vein endothelial cells (HUVECs) being used (83,84) or endothelial cells derived from pluripotent stem cells (72,85). Importantly, data indicates that the addition of these different cell types can promote hepatocyte maturation and metabolic competence in vitro (32,68,71,72,(78)(79)(80)(82)(83)(84)(85)(86) and, therefore, may be important for detecting some mechanisms of DILI.…”
Section: Establishing In Vitro Liver Models Using Human-based Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it has been reported that the hepatic phenotype of 3D-cultured spheroids is well maintained during long-term culture (for at least 35 days), as evidenced by well-sustained ATP levels, albumin secretion, and the overall stability of CYP enzyme activities [ 46 ]. Moreover, Bell et al evaluated acetaminophen-induced hepatotoxicity using a 3D co-culture system of PHHs and non-parenchymal cells, noting that high-level expression of miRNAs involved in the toxicity, i.e., mi-382 and mi-155, was observed [ 47 ]. In addition, to evaluate the potential of their system as a predictive model for drug-induced hepatotoxicity, they compared three emerging cell systems: hepatocytes derived from induced pluripotent stem cells, HepaRG cells, and PHH spheroids, at the transcriptional and functional levels in a multicenter study [ 48 ].…”
Section: Recent 3d-culture Studies Using Phhs For Hepatotoxicity Dmentioning
confidence: 99%
“…Cultured human cancer-derived hepatocytes have long been used for human-specific toxicity assessments, but they generally have lower expression levels of drug-metabolizing enzymes than PHHs [ 39 , 40 ]. Various applications of PHH spheroids as pharmacokinetic models [ 41 , 42 , 43 , 44 ] or hepatotoxicity detection models [ 16 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] have already been reported, and it has become clear that this model is extremely versatile and offers a variety of advantages over 2D cultures ( Table 2 ) [ 16 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. PHH spheroids have also been used as disease models [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%